Chicken soup for the teacher's soul : stories to open the hearts and rekindle the spirits of educators - Canfield, Jack, 1944-; Hansen, Mark Victor (Deerfield Beach, FL : Health Communications, 2002)
Presents over ninety short inspirational stories by teachers, counselors, administrators, educational consultants, and former students that provide insight into the joys and challenges of teaching.
Adult
Adult
Keywords: Teachers -- Conduct of life; Teaching -- Moral and ethical aspects; Teachers -- Conduct of life; Teaching -- Ethical aspects